Protest, youth and precariousness : the unfinished fight against austerity in Portugal - Carmo, Renato Miguel do, 1971-; Simões, José Alberto Vasconcelos (Protest, culture and society ;, 2020)
"After over a decade of the austerity measures that followed the 2008 financial crisis-entailing severe, unpopular policies that have galvanized opposition and frayed social ties-what lies next for European societies? Portugal offers an interesting case for exploring this question, as a nation that was among the hardest hit by austerity and is now seeking a fresh path forward. This collection brings together sociologists, social movement specialists, political scientists, and other scholars to look specifically at how Portuguese youth have navigated this politically and economically difficult period, negotiating uncertain social circumstances as they channel their discontent into protest and collective action"--